COVID 19 infection: Pediatric perspectives. Issue 1 (29th January 2021) - Adeyinka, Adebayo; Bailey, Keneisha; Pierre, Louisdon; Kondamudi, Noah
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has rapidly spread across the globe, causing innumerable deaths and a massive economic catastrophe. Exposure to household members with confirmed COVID‐19 is the most common source of infection among children. Children are just as likely as adults to get infected with SARS‐CoV‐2. Most children are asymptomatic and when symptoms occur, they are usually mild. Infants <12 months old are at a higher risk for severe or critical disease. COVID‐19 is diagnosed the same way in pediatric population as adults by testing specimen obtained from upper respiratory tract for nucleic acid amplification test (NAAT) using reverse transcriptase viral polymerase chain reaction (RT‐PCR). The common laboratory findings in hospitalized patient include leukopenia, lymphopenia, and increased levels of inflammatory markers. Chest X‐ray findings are variable and computed tomography scans of the chest may show ground glass opacities similar to adults or non‐specific findings. Prevention is the primary intervention strategy. Recently the U.S. Food and Drug Administration (FDA) has provided emergency authorization of the Pfizer‐BioNTech COVID‐19 vaccine and many other vaccine candidates are in the investigational stage. There is limited data in children on the use of antivirals, hydroxychloroquine, azithromycin, monoclonal antibody, and convalescent plasma. Oxygen therapy is required in hypoxic children (saturation <92%). Similar to adults, other measures to maintain oxygenation such as high flow nasal cannula, CPAP, or ventilatory support may be needed. Ventilatory management strategies should include use of low tidal volumes (5–6 cc/kg), high positive expiratory pressure, adequate sedation, paralysis, and prone positioning. Recently, a new entity associated with COVID‐19 called multisystem inflammatory syndrome in children (MIS‐C) has emerged. Clinical, laboratory, and epidemiological criteria are the basis for this diagnosis. Management options include ICU admission, steroids, intravenous gamma globulin, aspirin, anakinra, and anticoagulants. Vasoactive‐inotropic score (VIS) is used to guide vasopressor support.